Koya DeLaney and the good girl blues - Greenfield, Eloise (New York : Scholastic, 1992)
Koya Delaney, an eleven-year-old African-American girl, has trouble expressing anger, until her cousin, a popular male singer, comes to town.
G5
Keywords: African Americans -- Fiction; Anger -- Fiction